Formulation of rice bran oil nanocosmeceutical lotion loaded with germinated brown rice extract - Saharudin, Siti Hajar (2015)
Synthetic active compounds have been widely incorporated in cosmetic products all over the world due to its low price as well as it is easy to earn. Despite its advantages, the use of synthetic compounds in a long time could affect consumers’ health. As an alternative, natural active compounds can be used since it is safe and good for health. The aim of this study is to formulate a natural plant based nanoemulsion which consist of rice bran oil (RBO) and germinated brown rice (GBR). RBO is oil that has been extracted from bran layer of rice kernel while GBR is brown rice that has undergone a germination process. Both RBO and GBR consist of compounds that could be a good antioxidant agent and excellent cosmeceutical supplement such as vitamin E, γ-aminobutyric acid (GABA), γ-oryzanol, and phenolic compounds. Phase diagram was constructed to determine the composition that will be used for nanoemulsion formulation. Three different types of non-ionic surfactants were tested to identify its ability to form stable system. The surfactants were polyoxyethylene sorbitan monolaurate (Tween 20), polyoxyethylene sorbitan monooleate (Tween 80), and polyoxyethylene sorbitan trioleate (Tween 85). These surfactants are widely used in topical products due to their excellent safety, effectiveness levels, and economical cost. The results showed that the system containing Tween 80 has larger isotropic region compared to Tween 20 and Tween 85 system. Thus, Tween 80 was selected as the surfactant for further study. The composition selected from Tween 80 ternary phase diagram has been modified by adding different concentrations of xanthan gum (0.2%, 0.4%, 0.6%,0.8%, and 1.0%). The droplet size and pH of the formulations did not affected by the xanthan gum concentration. However, increasing the concentration of xanthan gum has increased the zeta potential, stability and rheological properties of the formulations. Consequently, xanthan gum plays a vital role in improving the physicochemical properties of the formulations. Three formulations were formulated with different concentrations of GBR extract (0%, 2% and 4%). The droplet size of the formulations decreased when GBR extract concentrations were increased. Meanwhile, increase in GBR extract has increased the zeta potential and stability of the formulations. The pH ranges of the formulations were in the skin’s pH range and all formulations have shear thinning behaviour. The study has found that GBR extract has an essential role in enhancing the characteristics of the formulations. Increase in GBR extract concentration in the formulations has increased the total phenolic content (TPC) and ferric reducing antioxidant power (FRAP) of the formulations. All formulations did not exhibit skin irritation potential. Additionally, all formulations possessed low skin lightening efficiency. Formulation without GBR extract did not have anti-inflammatory effect. Whereas formulations with 2% and 4% of GBR extract possesses low anti-inflammatory effect. Besides that, all formulations did not have anti-microbial properties. Formulation loaded with 4% of GBR extract was better compared to two other formulations in terms of it characteristic and cosmeceutical efficacy. As the conclusion, formulations modified with xanthan gum and loaded with GBR extract have been successfully formulated and characterized. Their potential cosmeceutical efficacies have also been profiled. However, additional in vitro and in vivo studies are recommended in order to further validate other potential cosmeceutical benefits of the RBO nanoemulsion and GBR extract on human skin.